Application of low-temperature plasma for the removal of copper chloride layers on bronze Wares - Ranran Jiao; Fuwei Sun; Jiaxing Li (Heritage Science, 2023)
Abstract Archaeological objects based on copper alloys (such as bronze wares) usually suffer from “bronze disease” that results from the existence of CuCl on the surfaces. The surface-coating Cu2(OH)3Cl can release Cl− and lead to further corrosion during the storage procedure. The central aim of the work is the verity the effectiveness of low-temperature radio-frequency (RF) plasma for the removal of CuCl and Cu2(OH)3Cl from the bronze wares. In this work, CuCl and Cu2(OH)3Cl patina were synthesized on copper by a simple solution method. The chemical and aesthetic features before and after plasma treatment were characterized using optical microscopy (OM), SEM-EDS, XRD, and XPS. The results show that Ar-H2 plasma could reduce the CuCl to Cu efficiently, which achieves pleasing esthetics as well as removes the chlorine (Cl atomic ratio decrease from 46.0 to 3.6%). For Cu2(OH)3Cl, the air plasma treatment exhibit better performance compared to the Ar-H2 plasma treatment, judging from the aesthetic effect and the removal effect of chlorine (Cl atomic ratio decrease from 14.8 to 3.3%).